Fluoroboro and Alkoxyboro-capped Encapsulated Compounds of Iron(II) Derived from Oxalodihydroxamic Acid - Rai, H.C.; Kumar, A.; Kumari, Veena (Asian Journal of Chemistry, 2010)
A fluoroboro-capped iron(II) clathrochelate was synthesized in one step reaction by combining iron(II), dihydroxamic acid and boron trifluoride in butanol medium followed by the addition of KOH dissolved in butanol. A series of alkoxyboro-capped iron(II) clathrochelates were also synthesized in one step reaction by combining iron(II), dihydroxamic acid and boric acid. The alkoxy groups were provided by the corresponding alcohol. Elemental analyses correspond to the stoichiometry, [FeL3(BX)2] L = Oxalodihydroximate ion, X = F, OC2H5, i-OC3H7 and n-OC4H9). The complexes have red to deep violet colour.